Determinants Of Accountability for Village Funds Management to Achieve Good Governance - Ingrid Permatasari; Hermawan; Siska (International Conference On Law And Social Sciences, 2024)
This research aims to determine and analyze both partial and simultaneous determinants of accountability for village funds management to achieve good governance in Bagan Sinembah Raya District. This research is empirical research using quantitative methods. The object of research is the village apparatus in the Bagan Sinembah Raya subdistrict with a total sampling method sample selection totaling 108 village officials. The data source used is primary data. A questionnaire is employed as the data-gathering tool. The data was analyzed using multiple approaches to linear regression analysis. The study's conclusions show how the degree of accountability in village funds management is influenced by the government's internal control system, the efficiency of the village apparatus, and the usage of information technology.